Pengaruh Likuiditas, Solvabilitas Dan Aktivitas Terhadap Profitabilitas: Studi Empiris pada Perusahaan Subsektor Kabel yang terdaftar di Bursa Efek Indonesia Tahun 2015-2020 - Argoputro, Stanislaus Bandung; Agustiani, Sabrina; Purba, Jan Horas Veryady (LPPM Institut Bisnis dan Informatika Kesatuan, 2023)
The conditions of competition in the business world experienced by companies are increasingly competitive in the era of globalization, including for companies in the cable sub-sector, thus requiring companies to be smarter in managing the ratios of financial statements in order to realize growing corporate profits. This industry contributes to the country's economy, one of which is the Indonesian capital market. Since 1990 the cable sub-sector has joined the Indonesian capital market with the aim of increasing the company's development by providing investment facilities. However, there were obstacles and a decline due to the Covid-19 pandemic in 2020, although the cable industry players were still able to operate after obtaining a Permit in accordance with the Circular Letter of the Minister of Industry. This study aims to analysis and obtain empirical evidence of the effect of current ratio, debt to asset ratio and working capital turnover on return on assets in cable sub-sector companies listed on the Indonesia Stock Exchange in 2015-2020. The data is taken through the financial statements of each cable sub-sektor company, as many as 36 samples are the criteria in this study. The data processing technique in this study used the EViews version 12 program. The result of the coefficient of determination shows the number 0.334240 or 33.42% the influence of the current ratio, debt to asset ratio and working capital turnover on return on assets. Simultaneously all independent variables used in this study have an influence on Return on Assets. Meanwhile, the partial test results show that the current ratio and debt to asset ratio have no significant effect on return on assets, while working capital turnover has a significant effect on return on assets. Keywords: Liquidity (CR), Solvency (DAR), Activity (WCT) and Profitability (ROA).